Epidemiologic studies of myasthenia gravis: literature review - T. M. Alekseeva; V. V. Kryuchkova; T. R. Stuchevskaya; A. N. Khalmurzina (Нервно-мышечные болезни)
The review of domestic and foreign literature devoted to epidemiological studies of myasthenia gravis has been reviewed. The article presents data on the prevalence and incidence of myasthenia gravis in several regions of Russia and abroad. The prevalence of myasthenia gravis in the world varies, according to different authors, in a very wide range – from 2.17 to 32.0 per 100 thousand people. There are few epidemiological studies of myasthenia gravis in large cities and regions of Russia. Meanwhile, studies of the prevalence and incidence of myasthenia gravis are a necessary stage in the work to increase the effectiveness of diagnosis and treatment of this pathology, to determine the need for specialized types of medical care. The results of these studies can be used to optimize the management of myasthenia gravis patients.